PENERAPAN PROJECT BASED LEARNING UNTUK MENINGKATKAN HASIL BELAJAR KOGNITIF SISWA - SITI SOLIHUN; AMINULLAH AMINULLAH (Universitas Mahasaraswati K. Mataram, 2023)
Cognitive learning outcomes are one measure of the success of learning in the classroom. Learning outcomes will be related to the learning environment and learning processes related to the learning methods applied by educators. Choosing an appropriate method in a learning environment requires a study or research. The aim of this research is to find out whether the project based learning method can improve students' cognitive learning outcomes. This type of research is Classroom Action Research (PTK) by measuring students' cognitive learning outcomes using multiple choice tests for high school level in Geography lessons. The research results show that the application of the project based learning method can improve students' cognitive learning outcomes both classically and individually. The increase in learning outcomes can be seen from the increase in student learning outcomes from an average of 75.24 to 76.67 and individually from a very high percentage of 14.29 to 23.81 with learning implementation of 86.66% to 93.33%.